Thickness-dependent quantum oscillations of the transport properties in bismuth selenide thin films - Rogacheva, E. I.; Menshikova, S. I.; Sipatov, A. Yu.; Nashchekina, O. N. (Elsevier, 2019)
The objects of the present study were thin n-Bi2Se3 films with thicknesses d = 10–100 nm, grown by thermal evaporation of n-Bi2Se3 crystals in vacuum onto heated glass substrates. The room temperature d-dependences of the Seebeck coefficient, the Hall coefficient, and the electrical conductivity of the films exhibited an oscillatory behavior, which we attribute to quantum size effects. Such interpretation of the results is supported by the fact that experimentally determined values of the oscillation period are in quite good agreement with the theoretically calculated ones. We suggest that the large amplitude and undamped character of the oscillations in the studied range of thicknesses are connected with the topologically protected gapless surface states of Bi2Se3. The observed oscillatory character of the d-dependences of the transport coefficients should be taken into account when 2D-structures are applied in nanothermoelectricity and other fields of nanoscience and nanotechnology.

Об’єктами дослідження були тонкі плівки n-Bi2Se3 товщиною d=10–100 нм, вирощені термічним випаровуванням кристалів n-Bi2Se3 у вакуумі на нагріті скляні підкладки. D-залежності коефіцієнта Зеєбека, коефіцієнта Холла та електропровідності плівок від кімнатної температури показали коливальну поведінку, яку ми приписуємо ефектам квантового розміру. Така інтерпретація результатів підтверджується тим, що експериментально визначені значення періоду коливань досить добре узгоджуються з теоретично розрахованими. Ми припускаємо, що велика амплітуда та незатухаючий характер коливань у осліджуваному діапазоні товщин пов’язані з топологічно захищеними безщілинними поверхневими станами Bi2Se3. Спостережуваний коливальний характер d-залежностей транспортних коефіцієнтів слід враховувати при застосуванні 2D-структур у нанотермоелектриці та інших галузях нанонауки та нанотехнологій.
Keywords: bismuth selenide; thin films; thermal evaporation; thickness; Seebeck coefficient; Hall coefficient; electrical conductivity; quantum size effect; topological insulator; вісмут селенід; тонкі плівки; термічне випаровування; товщина; коефіцієнт Зебека; коефіцієнт Холла; електрична провідність; ефект квантового розміру; топологічний ізолятор